2021
DOI: 10.3390/universe7050150
|View full text |Cite
|
Sign up to set email alerts
|

Minisuperspace Quantization of f(T, B) Cosmology

Abstract: We discuss the quantization in the minisuperspace for the generalized fourth-order teleparallel cosmological theory known as fT,B. Specifically we focus on the case where the theory is linear on the torsion scalar, in that consideration we are able to write the cosmological field equations with the use of a scalar field different from the scalar tensor theories, but with the same dynamical constraints as that of scalar tensor theories. We use the minisuperspace description to write for the first time the Wheel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…At the same time, it has been revealed that torsion and boundary term affects the thick brane scenario [38]. Paliathanasis [39] obtained the solution of the gravitational equations and investigated the existence of quantum corrections for the gravitational field equations. Hence, we are here motivated to study the late time cosmic acceleration issue in the f (T, B) gravity with some form of the Hubble function.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it has been revealed that torsion and boundary term affects the thick brane scenario [38]. Paliathanasis [39] obtained the solution of the gravitational equations and investigated the existence of quantum corrections for the gravitational field equations. Hence, we are here motivated to study the late time cosmic acceleration issue in the f (T, B) gravity with some form of the Hubble function.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nonzero spatial curvature was recently considered in [63]. The minisuperspace quantization in f (T, B) was studied in [64] while an inhomogeneous exact solution was recently found in [65]. The recent work [66] deals with the study of anisotropic solutions in f (T, B).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a closed Friedmann-Lemaître-Robertson-Walker (FLRW) spacetime with a quintessence scalar field as a matter source, the WDW equation was studied independently by Hartle and Hawking in [10] and Vilenkin in [11]. Since then, similar approaches have been widely applied in the literature for many other cosmological models with a minisuperspace description; see for instance [12][13][14][15][16][17][18][19] and references therein. Nonetheless, the canonical quantization proposal founded in the initial works by DeWitt and Wheeler is not the unique approach towards quantum cosmology, other attempts are based in string theory [20][21][22] and in loop quantum gravity [23,24].…”
Section: Introductionmentioning
confidence: 99%

Quantum Cosmology in $f(Q)$ theory

Dimakis,
Paliathanasis,
Christodoulakis
2021
Preprint